HUBUNGAN KARAKTERISTIK DENGAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS PIR II BAJUBANG KABUPATEN MUARO JAMBI - Era Meganovitri; Krisdiyanta; Mualim, Mualim (Jurnal Sanitasi Profesional Indonesia, 2024)
Community characteristics contribute greatly to waste management. The characteristics of the community in the working area of ​​the Bajubang PIR II Community Health Center are very varied. The aim of the research is to determine the relationship between community characteristics and community participation in managing household waste in the PIR II Bajubang Community Health Center Working Area, Muaro Jambi Regency. The research method used is quantitative using an observational analytical design, in accordance with the research objective which is to explain the relationship between variables. The research location is in the PIR II Bajubang Health Center Working Area, Muaro Jambi Regency. The population is 2,322 housewives with a research sample of 92 housewives The instruments used were: questionnaire and checklist. Data analysis used the statistical test used was Chi-Square with a confidence level of 95% where α = 0.05. The results of the study showed that no Chi-square statistical test results were calculated because the respondents' attitudes towards the environment were constant, namely good for all, while family members had nothing to do with community participation. Meanwhile, other individual characteristic variables were significantly related to community participation in waste management. . Conclusion: The dominant characteristics of community participation in managing household waste in the PIR II Bajubang Community Health Center Working Area, Muaro Jambi Regency. The results of multivariate analysis using logistic regression statistical tests showed that the most dominant variables were the education variable and the income variable had a p value <0.05.